Sharing Economy of Islamic Microfinance & Its Impact on Social & Financial Inclusion: Social Capital Matter? - Yulizar Djamaluddin Sanrego (SMART Insight, 2023)
The significant role of Islamic microfinance is how they could articulate the colloborative nature of Islamic moral economy in the form ukhuwwah (social capital) among the poor participants’ program. Sharing or collaborative economy in this business platform is how poor participants of Islamic microfinance-group lending model (GLM) based, which considered as unbankable or even un-bmtable share they risk, having mutual trust, cooperative, collective responsibility to have an access to social as well as financial services provided by any form of philanthropy aids. The existence of ukhuwwah (social capital) would become critical informal institutional values that leads to an efficient sharing or collaborative business among the poor participants. The aims of the paper is to highligt the effectiveness of Islamic microfinance-group lending model (GLM) based in Cooperative Empowerment of Baitut Tamkin Tazkia Madani (BTTM) to establish social capital in supporting sharing economy and hence promoting the achievement of social and financial inclusion of the poor participants. Therefore, any kinds of philanthropy for humanitarian aid (including ZISWAH) should pay critical attention to the existence of social capital in order to alleviate poverty as well as to maintain human dignity.